Anxiety due to Dental Treatment and Procedures among University Students and Its Correlation with Their Gender and Field of Study - Mohd G. Sghaireen; Abdalwhab M. A. Zwiri; Ibrahim A. Alzoubi; Sadeq M. Qodceih; Mahmoud K. AL-Omiri (Hindawi Limited, 2013)
Aim of Study. To investigate dental anxiety levels among university students and its relation with their specialty and gender. Materials and Methods. 850 undergraduate university students were recruited into the study. The Modified Corah Dental Anxiety Scale (MDAS) was used to measure the levels of their dental anxiety. 700 questionnaires were returned, 390 females and 310 males (response rate of 0.92% among females, 0.73% among males). The MDAS score ranged from 5 to 25. Patients were considered to suffer from high dental anxiety if they scored 13 to 20 points. Statistical analysis significance was set at P≤0.05. Results. Seven hundred students participated in this study including 13% of medical students, 10% of dental students, 58% of arts students, and 18% of computer science students. Medical and dental students were less anxious than arts and computer science students (P<0.05). Local anesthesia injection was the most fearful dental procedure (P<0.05). Females were more anxious than males (P<0.05). Conclusion. Male students were less anxious than female students. Students from medical background faculties were less anxious than students from nonmedical faculties. Lack of adequate dental health education may result in a higher level of dental anxiety among nonmedical students in Saudi Arabia.